Forced regressive deposits of a deglaciation sequence: Example from the Late Quaternary succession in the Lake Saint‐Jean basin (Québec, Canada). Issue 6 (23rd March 2015) - Nutz, Alexis; Ghienne, Jean‐François; Schuster, Mathieu; Dietrich, Pierre; Roquin, Claude; Hay, Murray B.; Bouchette, Frédéric; Cousineau, Pierre A.; Eyles, Nick
Abstract Differentiating between forced regressive deposits from deglacial periods in high latitude domains and forced regressive deposits from the onset of glacial periods in low latitude domains is fundamental for the accurate interpretation of glacial cycles within the geological record and then for the reconstruction of palaeogeography and palaeo‐climate. A forced regressive deglacial sequence is documented from the Lake Saint‐Jean basin (Québec, Canada). In this area, the Late Pleistocene to Holocene sediments have recorded the Laurentide ice sheet retreat accompanied by the invasion of marine waters (Laflamme Gulf) from ca 12·9 cal kyr bp. Subsequently, fluvio‐deltaic and coastal prograding wedges were deposited; they followed the base‐level fall due to glacio‐isostatic rebound. This succession, representing a transition from glacial to post‐glacial periods within a previously glaciated area, was investigated through recent mapping, preserved landforms, facies analysis, and new optical stimulated luminescence and radiocarbon dates. Three basin‐scale geological sections share a common lower part made of isolated ice‐contact fan deposits overlying bedrock. Throughout the entire basin, ice‐contact fans are capped by glacimarine muds. Above, fluvial and coastal prograding systems were deposited and evolved through four steps: (i) deltaic systems progressively increased in width; (ii) coastal influence on sedimentation increased; (iii) hydrographic drainage systems became more organised; and (iv) deltas graded from steep (Gilbert delta) to low‐angle foresets (mouth‐bar delta). Deposited during the base‐level fall from glacio‐isostatic rebound, the complete succession has been designated as a single falling stage system tract referred to as a deglacial falling stage system tract. It is representative of a deglaciation sequence in areas previously covered by ice during glacial periods (i.e. medium to high latitude domains). Diagnostic criteria are provided to identify such a deglacial falling stage system tract in the geological record, which may aid identification of previously unknown glacial cycles.